2021
DOI: 10.3390/bioengineering8110171
|View full text |Cite
|
Sign up to set email alerts
|

Interferences of Waxes on Enzymatic Saccharification and Ethanol Production from Lignocellulose Biomass

Abstract: Wax is an organic compound found on the surface of lignocellulose biomass to protect plants from physical and biological stresses in nature. With its small mass fraction in biomass, wax has been neglected from inclusion in the design of the biorefinery process. This study investigated the interfering effect of wax in three types of lignocellulosic biomass, including rice straw (RS), Napier grass (NG), and sugarcane bagasse (SB). In this study, although small fractions of wax were extracted from RS, NG, and SB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Herein, wax interferences were then investigated to improve the saccharification efficiency. Research showed that dewaxing biomass resulted in increased sugar and ethanol yields with all tested lignocellulosic biomasses [6]. Furthermore, the extracted wax from raw biomass was analyzed by GC-MS.…”
Section: Renewable Bioethanol From Lignocellulosementioning
confidence: 99%
See 1 more Smart Citation
“…Herein, wax interferences were then investigated to improve the saccharification efficiency. Research showed that dewaxing biomass resulted in increased sugar and ethanol yields with all tested lignocellulosic biomasses [6]. Furthermore, the extracted wax from raw biomass was analyzed by GC-MS.…”
Section: Renewable Bioethanol From Lignocellulosementioning
confidence: 99%
“…Furthermore, the extracted wax from raw biomass was analyzed by GC-MS. The researchers identified the major composition of fatty acid methyl esters and other valuable compounds, attributes that enhance its value on market and potential for future commercialization [6].…”
Section: Renewable Bioethanol From Lignocellulosementioning
confidence: 99%
“…The liquid fraction of hydrolysate (without the addition of sodium azide) was subjected to fermentation for ethanol production using yeast, Saccharomyces cerevisiae TISTR 5606 [18][19]. For each experiment, 5% of yeast inoculum (at the concentration of about 10 8 cells/ml) was added to 19 ml of rice straw hydrolysate supplemented with 1%w/v glucose and 1% w/v yeast extract [18,19]. The sample was incubated in a shaking incubator at 30 o C, 150 rpm for 72 h. Then, the supernatant fraction of yeast culture was separated by centrifugation at 8,000 xg for 10 min.…”
Section: Ethanol Fermentationmentioning
confidence: 99%